Anti-Streptolysin O in Human Immunodeficiency Virus Patients - Setiawan, Doni; Nurmalasari, Ary; Ridla Firdaus, Nabil; Maulana, Ilham (LPPM STIKes Muhammadiyah Ciamis, 2024)
Human Immunodeficiency Virus (HIV) is a pathogenic virus that attacks and damages the human immune system so that the body becomes weak in fighting viral or bacterial infections. The purpose of this study was to determine the description of Anti Streptolysin O examination in HIV patients at Imbanagara Health Center. This research method is descriptive, with a sample size of 35 HIV-positive people in Imbanagara. Measurements used qualitative and semi-quantitative procedures with a black background slide instrument. The examination was conducted at the Imbanagara Health Center in June 2023. The results of this study obtained positive results for as many as three people (9%) with an average ASTO level of 400 IU/mL and negative results for as many as 32 people (91%).